Healthy Living: Diabetes - Linda B. Bobroff; Paulina Wittkowsky (EDIS)
Revised! FCS8575, a 1-page handout by Linda B. Bobroff and Paulina Wittkowsky, answers basic questions about diabetes in an easy-to-read format. Published by the UF Department of Family Youth and Community Sciences, March 2010.